Coupling solar‐driven interfacial evaporation with forward osmosis for continuous water treatment. Issue 4 (6th July 2022) - Song, Xiangju; Dong, Weichao; Zhang, Yajing; Abdel‐Ghafar, Hamdy Maamoun; Toghan, Arafat; Jiang, Heqing
Abstract: Forward osmosis (FO) driven by osmotic pressure difference has great potential in water treatment. However, it remains a challenge to maintain a steady water flux at continuous operation. Herein, a FO and photothermal evaporation (PE) coupling system (FO‐PE) based on high‐performance polyamide FO membrane and photothermal polypyrrole nano‐sponge (PPy/sponge) is developed for continuous FO separation with a steady water flux. The PE unit with a photothermal PPy/sponge floating on the surface of draw solution (DS) can continuously in situ concentrate DS by solar‐driven interfacial water evaporation, which effectively offsets the dilution effect due to the injected water from FO unit. A good balance between the permeated water in FO and the evaporated water in PE can be established by coordinately regulating the initial concentration of DS and light intensity. As a consequence, the polyamide FO membrane exhibits a steady water flux of 11.7 L m –2 h –1 over time under FO coupling PE condition, effectively alleviating the decline in water flux under FO alone. Additionally, it shows a low reverse salt flux of 3 g m –2 h –1 . The FO‐PE coupling system utilizing clean and renewable solar energy to achieve a continuous FO separation is significantly meaningful for practical applications. Abstract : A forward osmosis and photothermal evaporation coupling system (FO‐PE) based on high‐performance polyamide FO membrane and photothermal polypyrrole nano‐Sponge (PPy/Sponge) is developed for continuous FO separation with a steady water flux. The FO‐PE coupling system utilizing clean and renewable solar energy to achieve efficient water treatment is significantly meaningful for practical applications.